(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Beta thalassemia major patients require lifelong repeated red blood cell transfusions, which predispose them to alloimmunization against foreign erythrocyte antigens. Development of alloantibodies complicates transfusion therapy and may lead to delayed hemolytic transfusion reactions and difficulty in obtaining compatible blood. This study was undertaken to evaluate the frequency and specificity of red blood cell alloantibodies in multitransfused β-thalassemia patients. Materials and Methods: This cross-sectional study was conducted at Dr. D. Y. Patil Medical College, Hospital and Research Centre, Kolhapur, over a period of three years. A total of 84 β-thalassemia patients who had received more than 10 packed cell transfusions were included. ABO and RhD blood grouping were performed using standard methods. Antibody screening was carried out using a commercial three-cell reagent panel, and positive samples were further evaluated with an 11-cell antibody identification panel using the gel card method. Results: Among the 84 multitransfused β-thalassemia patients, 10 patients were positive for red cell alloantibodies, giving an overall alloimmunization prevalence of 11.90%. The majority of alloantibodies belonged to the Kell blood group system, with Anti-K being the most frequently detected antibody (40%), followed by Anti-e (20%). Other antibodies identified included Anti-k, Anti-D, antibodies against Jsb, kpb, Lub, and MNS system antibodies. No statistically significant association was observed between alloimmunization and age, gender, or splenectomy status. Conclusion: Red cell alloimmunization remains a significant complication in transfusion-dependent β-thalassemia patients. The predominance of Kell and Rh alloantibodies highlights the importance of extended antigen phenotyping and provision of phenotype-matched blood from the initiation of transfusion therapy. Early screening and preventive transfusion strategies can substantially reduce alloimmunization and improve transfusion safety in thalassemia patients.